The impact of standard operating procedures and turnover intention on employee performance at PT Albany Corona Lestari Tangerang Branch - Abdul Rahman Safiih; Ahmad Husaini (Institute of Accounting Research and Novation (IARN), 2025)
This study aims to analyze the effect of Standard Operating Procedures (SOP) and Turnover Intention on Employee Performance at PT Albany Corona Lestari, Tangerang Branch 1. The research employed a quantitative method with saturated sampling, involving the entire population of 67 employees as respondents. Data were collected through questionnaires and analyzed using validity and reliability tests, simple linear regression, multiple linear regression, t-test, and F-test. The findings indicate that: (1) SOP has a positive and significant effect on employee performance with a significance value of 0.027 and a contribution of 7.3%. The simple regression equation Y = 16.321 + 0.251X1 means that each one-unit increase in SOP will improve performance by 0.251 points. (2) Turnover Intention has a positive and significant effect on employee performance with a significance value of 0.002 and a contribution of 14.1%. The simple regression equation Y = 15.944 + 0.243X2 implies that each one-unit increase in turnover intention raises performance by 0.243 points. (3) SOP and Turnover Intention simultaneously have a significant effect on employee performance with a significance value of 0.001 and a contribution of 20.7%. The multiple regression equation Y = 11.085 + 0.238X1 + 0.236X2 suggests that improvements in SOP and turnover intention together contribute to higher employee performance. These findings highlight the importance of consistent SOP implementation and effective turnover intention management to maintain optimal employee performance in achieving organizational goals.